2011
DOI: 10.1590/s1516-35982011000500001
|View full text |Cite
|
Sign up to set email alerts
|

True and apparent digestibility of protein and amino acids of feed in Nile tilapia

Abstract: -It was determined in this work the coefficients of apparent and true digestibility of protein and amino acids of five feeds (corn, wheat bran, soybean meal, corn gluten meal, fish meal) in Nile tilapia. It was used 252 reverted Thai strain Nile tilapia (Oreochromis niloticus) in growth phase, with weight of 310 ± 9.68 g, distributed in experimental randomized blocks design, with five treatments, six replicates per treatment and seven fish per experimental unit. Each experimental diet contained a single source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
8
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
(41 reference statements)
6
8
2
2
Order By: Relevance
“…The digestibility coefficient of threonine for soybean meal, corn gluten meal, corn flour and wheat bran values found in this study were similar to those obtained by Ribeiro et al (2011Ribeiro et al ( , 2012 for tilapia, with the ADC of threonine varying between 73.0% to 90.3%. Although silver mojarra is an omnivorous species, the digestibility coefficient of threonine for fish meal was similar to that reported by Davies et al (2009) for carnivorous marine species such as turbot, bream and European seabass, with the ADC exceeding 88%.…”
Section: Apparent Digestibility Coefficients Of Amino Acids (Adcaa)supporting
confidence: 86%
See 1 more Smart Citation
“…The digestibility coefficient of threonine for soybean meal, corn gluten meal, corn flour and wheat bran values found in this study were similar to those obtained by Ribeiro et al (2011Ribeiro et al ( , 2012 for tilapia, with the ADC of threonine varying between 73.0% to 90.3%. Although silver mojarra is an omnivorous species, the digestibility coefficient of threonine for fish meal was similar to that reported by Davies et al (2009) for carnivorous marine species such as turbot, bream and European seabass, with the ADC exceeding 88%.…”
Section: Apparent Digestibility Coefficients Of Amino Acids (Adcaa)supporting
confidence: 86%
“…The ADC of methionine for corn meal, fish meal and soybean meal varied between 92.8% and 94.2%. These values are higher than those found by Ribeiro et al (2011), who studied the same ingredients in the Nile tilapia, and found a mean apparent digestibility of methionine between 79.6% and 91.1%. Ingredients with a high digestibility of methionine as mentioned above should be provided preferably during periods of spawning and reproduction.…”
Section: Apparent Digestibility Coefficients Of Amino Acids (Adcaa)contrasting
confidence: 68%
“…Essential and nonessential amino acids ADC were similar (P>0.05) for the cultivars orelha de onça, IPA 20 and comum, with exception for phenylalanine and tyrosine (Table 5). Among the essential amino acids, arginine presented higher ADC, corroborating the results obtained for Nile tilapia by Santos et al (2010), who studied forage radish bran; Freire, Barros and Pezzato (2005) using low tannin sorghum and Ribeiro et al (2011) for soybean bran, corn gluten and fishmeal. Cultivars orelha de onça, miúda, IPA 20 and comum presented higher (P<0.05) arginine ADC in relation to the cultivar gigante.…”
Section: Resultssupporting
confidence: 85%
“…The optimal value of digestible protein of a given raw material in fish feed ranged from 75 to 95% (NRC, 2011). The protein digestibility of C. lentillifera powder was not significantly different compared to those of white pollard (83.87%), soybean meal (91.12%), and fish meal (83.53%) (Ribeiro et al, 2011).…”
Section: Discussionmentioning
confidence: 74%